Mixed methods perspectives on communication and social media research - Segumpan, Reynaldo Gacho; Soraya Abu Zahari, Joanna (New York: Routledge, 2023)
"Mixed Methods Perspectives on Communication and Social Media Research addresses the need for a discipline-cum-methodology-tailored book that navigates the current research spectrum of communication and social media ("CommSocMed"). It examines contemporary and relevant issues that intertwine the expansive spheres of CommSocMed"--
Includes bibliographical references and index.
Keywords: Social media -- Research -- Methodology; Communication -- Research -- Methodology